alpha-tocopherol as a modulator of smooth muscle cell proliferation - (:unkn) unknown (ELSEVIER SCI LTD, 1997)
The effects of alpha-tocopherol and beta-tocopherol have been studied in rat and human aortic smooth muscle cells. alpha-tocopherol, but not beta-tocopherol, inhibited smooth muscle cell proliferation and protein kinase C in a dose-dependent manner, at concentrations ranging from 10 to 50 mu M. beta-tocopherol added simultaneously with alpha-tocopherol prevented both proliferation and protein kinase C inhibition. Protein kinase C inhibition was cell cycle-dependent and it was prevented by okadaic acid, a protein phosphatase inhibitor. Protein kinase C activity measured from aortas of cholesterol-fed rabbits was also inhibited by alpha-tocopherol. By using protein kinase C (PKC) isoform-specific inhibitors and immunoprecipitation reactions it was found that PKC-alpha was selectively inhibited by alpha-tocopherol. Further, an activation of protein phosphatase 2A by alpha-tocopherol was found, which caused PKC-alpha dephosphorylation and inhibition. Ultimately, this cascade of events at the level of cell signal transduction leads to the inhibition of smooth muscle cell proliferation.
Keywords: PROTEIN-KINASE-C; VITAMIN-E CONSUMPTION; CORONARY-DISEASE; CAROTID-ARTERY; ATHEROSCLEROSIS; ANTIOXIDANT; INHIBITION; RAT; PATHOGENESIS; PROGRESSION